English Composition 1 - TR246 - 202101 - Universidad Peruana de Ciencias Aplicadas (UPC) (2021)
English Composition 1 familiarizes students with the social and situated nature of writing--that is, with the ways in which writing is tied to purpose, audience/community, and topic/content. It is designed specifically for students writing in English as an additional language.